2015
DOI: 10.1111/are.12876
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia on lysozyme activity and antioxidant defences in the kidney and spleen ofCarassius auratus

Abstract: Assessing the responses of lysozyme activity and antioxidant defences to hypoxia is important to understand the adaptation and tolerance strategies of fish under hypoxia. This study investigated the effects of different dissolved oxygen (DO) levels on Carassius auratus, a natural triploid fish, from Qihe River. The content of malondialdehyde (MDA) and the activities of lysozyme and antioxidant enzymes were measured in the kidney and spleen after hypoxic exposure. At the DO concentrations of 1 and 2 mg L À1 , t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 80 publications
3
9
0
Order By: Relevance
“…The rise in the liver MDA content of GIFT juveniles could signal a massive production of lipid peroxidation (LPO) (Hegazi et al., 2010) resulting from the hypoxia‐induced oxidative stress. Similar results were reported on Carassius auratus (Zhao et al., 2017) and sea cucumber Apostichopus japonicas (Huo et al., 2018). Avellini et al.…”
Section: Discussionsupporting
confidence: 87%
“…The rise in the liver MDA content of GIFT juveniles could signal a massive production of lipid peroxidation (LPO) (Hegazi et al., 2010) resulting from the hypoxia‐induced oxidative stress. Similar results were reported on Carassius auratus (Zhao et al., 2017) and sea cucumber Apostichopus japonicas (Huo et al., 2018). Avellini et al.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that MDA accumulation is positively related to the level of oxidative stress ( Shi et al, 2005 ; Sun et al, 2008 ). Moreover, significantly increased content of MDA was observed in Carassius auratus under hypoxia ( Zhao et al, 2017 ). In the present study, the content of MDA in coelomic fluid from sea cucumber increased about twofold under hypoxia, suggesting that hypoxia stress caused lipid peroxidation resulting from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic hypoxia induces changes in the fish immune system, involving cytokines, granulocytes, and macrophages [ 4 6 ]. Slight hypoxic stress can elevate non-specific immune responses in fish, but severe hypoxic challenge results in immunosuppression [ 7 , 8 ]. Therefore, hypoxia is now considered as a potential regulator of immunity.…”
Section: Introductionmentioning
confidence: 99%